Explaining high external efficacy in authoritarian countries: a comparison of China and Taiwan. Issue 2 (23rd February 2017) - Zhou, Yingnan Joseph; Ou-Yang, Ray
ABSTRACT: We examine the puzzling phenomenon that authoritarian governments are perceived to be more responsive than democratic governments. By comparing China and Taiwan by both large-N statistical analyses and in-depth case studies, we show that the answer lies in the differences between democratic and authoritarian institutions. First, failing to elect one's preferred candidate in democracies predisposes voters to critical assessment of government responsiveness. There is no such predisposition in authoritarian countries where elections are nonexistent or nominal. Second, elections incentivize democratic leaders to over-respond to certain groups. There is no such mechanism in authoritarian countries. Third, the solid and clear legitimacy established by electoral victories shield democratic leaders from particularistic demands made through unconventional channels. Without such legitimacy, authoritarian leaders are compelled to cement legitimacy by increasing responsiveness.